A Piecewise Model for In Situ Raman Measurement of the Chlorinity of Deep-Sea High-Temperature Hydrothermal Fluids. Issue 9 (September 2021) - Ge, Meng; Li, Lianfu; Zhang, Xin; Luan, Zhendong; Du, Zengfeng; Xi, Shichuan; Yan, Jun
The chlorinity of deep-sea hydrothermal fluids, representing one of the crucial deep-sea hydrothermal indicators, indicates the degree of deep phase separation of hydrothermal fluids and water/rock reactions. However, accurately measuring the chlorinity of high-temperature hydrothermal fluids is still a significant challenge. In this paper, a piecewise chlorinity model to measure the chlorinity of high-temperature hydrothermal fluids was developed based on the OH stretching band of water, exhibiting an accuracy of 96.20%. The peak position, peak area ratio, and F value were selected to establish the chlorinity piecewise calibration model within the temperature ranges of 0–50 ℃, 50–200 ℃, and 200–300 ℃. Compared with that of the chlorinity calibration model built based on a single parameter, the accuracy of this piecewise model increased by approximately 4.83–12.33%. This chlorinity calibration model was applied to determine the concentrations of Cl for high-temperature hydrothermal fluids in the Okinawa Trough hydrothermal field. Graphical Abstract